Nowe znaleziska naparstków ze stanowiska archeologicznego przy ulicy 3 Maja w Gdańsku – przyczynek do krawiectwa gdańskiego - Wołyńska, Marta (In Gremium. Studies in History, Culture and Politics, 2013)
New discoveries of fingerstalls at archaeological site at 3 Maja Street in Gdańsk as the contribution to Gdańsk’s tail oring. This paper discusses a proposal of fingerstalls typology based on the differences in their form and decoration. It further shows changes visible concurrently in both historical and archaeological sources. The author isolates four internally varied types of artefacts dated to the 16th-17th centuries. The author underlines the richness of decorative motives, analyses signatures known from monuments and compares them with cachets. The author also discusses the issue of universality of the basic relic in tailoring with reference to social, cultural, and economic changes in the city of Gdańsk registered in historical sources. The multilayer local development inspired with numerous external contacts within the Hanseatic League as well as Gdańsk’s relation with western European countries in the early modernity are discussed herein. The signs of them are clear in the sources of material adoption of ideas, styles as well as numerous imports.